Those Led-Lit Water-Kooled Multi-Screen Streamline Battlestations - Gibbs, Martin; Carter, Marcus; Nansen, Bjorn (AoIR Selected Papers of Internet Research, 2017)
Battlestations are customized desktop computers, typically devoted to gaming. In this paper we present analysis of the all-time top 50 up-voted battlestations on the /r/battlestations subreddit. Through an examination of these highly commended battlestations and the community criteria defining a “good” battlestation we provide insights into the material culture of computer customization and its significance within internet gaming sub-cultures.